WeeliciousCuisine quick response (QR) - Khong, Yeen Lai; Low, Suet Cheng; Lee, Sin Yee; Lim, Wan Leng; Tee, Peck Ling (2015)
This paper attempts to create a WeeliciousCuisine quick respond (QR) code content which including some guideline video to guide the users on how to use this product and also providing some recipe to teach them how to used and how to made a complete dishes.The target of audience ages are in seventeen to twenty five years old.Besides that, it also aim for the restaurants, shops and bars to provide them a better understanding of how the products have been use as to improve the services of the tourism industry as this application provides the useful information related to the products or ingredients that required by the foreigners, so the users can get the right ingredients in overseas for example, Malaysia.Research conducted by using the descriptive statistics and result shown more than 58% respondents are still not familiar with Quick respond code but more than a half respondents are interested to know more about Quick respond code and requested to improve their content on food and beverage.In conclusion, WeeliciousCuisine Quick Response (QR) is a system that helps user to have a quick look and learn how to cook in short time.The function of this system is to prevent users for choosing the wrong ingredients and also help them to save time and cost in the supermarket.